BUILDING MATERIALS SALES SYSTEM APPLICATION PDA UD.ANNIEZH BY USING MICROSOFT VISUAL FOXPRO 9.0 - Arnis Setiana; Ristyawati, SKom, MMSI Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2010)
On the application of sales and sales reports provide convenience to the user to input the data and then process them and produce desired outputs. In the implementation of data processing using computer applications using Microsoft Visual FoxPro 9.0. The sales process is still manual UD.Anniezh previously experienced many difficulties in implementing the sales process, especially in making sales report that is less accurate, effective and efficient. Therefore,  the authors tried to make an application program on UD.Anniezh sales system by utilizing the facilities available in Microsoft Visual FoxPro 9.0 to make the sales process and simplify the checkout in the preparation of reports to be submitted to the leaders.